The Coxiella burnetii T4SS Effector AnkF Is Important for Intracellular Replication - Pechstein, Julian; Schulze-Luehrmann, Jan; Bisle, Stephanie; Cantet, Franck; Beare, Paul A.; Ölke, Martha; Bonazzi, Matteo; Berens, Christian; Lührmann, Anja (Frontiers in Cellular and Infection Microbiology, 2020)
Coxiella burnetii is an obligate intracellular pathogen and the causative agent of the zoonotic disease Q fever. Following uptake by alveolar macrophages, the pathogen replicates in an acidic phagolysosomal vacuole, the C. burnetii-containing vacuole (CCV). Effector proteins translocated into the host cell by the type IV secretion system (T4SS) are important for the establishment of the CCV. Here we focus on the effector protein AnkF and its role in establishing the CCV. The C. burnetii AnkF knock out mutant invades host cells as efficiently as wild-type C. burnetii, but this mutant is hampered in its ability to replicate intracellularly, indicating that AnkF might be involved in the development of a replicative CCV. To unravel the underlying reason(s), we searched for AnkF interactors in host cells and identified vimentin through a yeast two-hybrid approach. While AnkF does not alter vimentin expression at the mRNA or protein levels, the presence of AnkF results in structural reorganization and vesicular co-localization with recombinant vimentin. Ectopically expressed AnkF partially accumulates around the established CCV and endogenous vimentin is recruited to the CCV in a time-dependent manner, suggesting that AnkF might attract vimentin to the CCV. However, knocking-down endogenous vimentin does not affect intracellular replication of C. burnetii. Other cytoskeletal components are recruited to the CCV and might compensate for the lack of vimentin. Taken together, AnkF is essential for the establishment of the replicative CCV, however, its mode of action is still elusive.